2019
DOI: 10.1186/s12877-019-1184-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent hypoxia-hyperoxia on mobility and perceived health in geriatric patients performing a multimodal training intervention: a randomized controlled trial

Abstract: Background Additional benefits of passive exposures to intermittent hypoxia and hyperoxia on cognitive performance and functional exercise capacity have been demonstrated in geriatric patients who performed a multimodal training program. The main goal of the present study was to evaluate effects of adding intermittent hypoxic-hyperoxic training (IHHT) to a multimodal training intervention (MTI) on mobility and perceived health in old individuals at a Geriatric Day Hospital. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
1
23
2
3
Order By: Relevance
“…These effects can be beneficial in the prevention and treatment of cardiovascular and brain diseases, such as AD [32,33,34,35,36]. Exercise combined with IHT additionally enhanced exercise performance and improved cognitive function in elderly individuals [37,38,39]. IHT also improved walking ability after chronic spinal cord injury [40].…”
Section: Introductionmentioning
confidence: 99%
“…These effects can be beneficial in the prevention and treatment of cardiovascular and brain diseases, such as AD [32,33,34,35,36]. Exercise combined with IHT additionally enhanced exercise performance and improved cognitive function in elderly individuals [37,38,39]. IHT also improved walking ability after chronic spinal cord injury [40].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the present study, the beneficial effect of IHHE on physical performance could be explained by specific cardiovascular and muscular adaptations, such as angiogenesis, improved glycose transport, glycolysis, and pH regulation as well as mitochondrial functioning ( Gore et al, 2007 ; Verges et al, 2015 ). Contrary, Bayer et al (2019) did not confirm the hypothesis that IHHE would significantly improve the efficiency of an individualized multimodal training program on functional mobility or physical performance in geriatric patients, operationalized by TUG, Tinetty Mobility Test, and Barthel Index. Interestingly, Bayer et al (2019) demonstrated improvements in all three tests in both groups, suggesting that the individualized multimodal training program was effective regardless of the addition of IHHE.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, 40 studies were examined for eligibility. Of these, 32 studies were excluded due to the following reasons: non-English full-text [ 79 – 82 ], duplicate data [ 72 74 ], investigating effects of IHHE or IHHT in animals [ 83 – 85 ], or did not meet the inclusion criteria with respect to the intervention (investigating only acute effects of IHHE or IHHT [ 64 , 65 , 86 88 ] or the effects of permanent or long-term stay in hypoxia or hyperoxia [ 89 92 ]), or the article type (i.e. not original article: narrative review [ 93 , 94 ], book chapter [ 95 ], or a conference abstract [ 96 – 105 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Studies matching one of these combinations were excluded from this systematic review. Three studies [ 72 74 ] were identified as duplicate category pattern three and were thus excluded from the final analysis (Fig. 2 ).…”
Section: Methodsmentioning
confidence: 99%